Overview of Blockchain Technology: Consensus, Architecture, and Its Future Trends (International Journal of Innovative Research in Computer Science & Technology, 2021)
The blockchain technology that underpins  Bitcoin has lately gained a lot of traction. Blockchain is a  decentralized transaction ledger that is immutable.  Blockchain applications are emerging in a variety of fields,  including financial services, reputation systems, and the  Internet of Things (IoT), among others. Nonetheless,  concerns with blockchain knowledge, like as security or  scalability, have yet to be solved. Bitcoin can only process  7 transactions per second, making it unsuitable for high frequency trading. Larger blocks, on the other hand, imply  more storage capacity and less network transfer. Because  fewer individuals desire to own such a large blockchain,  this will ultimately lead to centralization. This article  provides a comprehensive description of blockchain  technology. The researcher first provides an overview of  blockchain architecture and then compares many commonly  utilized consensus algorithms in different blockchains. A  brief summary of technical difficulties and current advances  is also included. They also highlight possible future  blockchain developments.
Keywords: Bitcoin; Block Chain; Consensus; Decentralization; Scalability